Makna Filosofis Sajen Pesta Laut Sukabumi: Analisis Semiotika dan Panca Curiga - Zulfan Ali Mujtaba; Juni Amanullah (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
This study examines the philosophical meaning of the sajen (offering) tradition at the Pesta Laut in Sukabumi Regency, which is often marginalized in modern discourse due to readings limited to assumptions of irrationality. Academically, the urgency of this research stems from the limitations of previous studies that generally focus on the sociological or ecological functions of coastal rituals but have not specifically integrated the analysis of sign structures with local epistemology. This study aims to fill this methodological gap by comprehensively deconstructing the symbolic meaning of sajen. Through a qualitative design based on literature study, this research integrates two analytical frameworks: Roland Barthes' semiotics to dissect the visual sign order, and the Panca Curiga methodology as a specific analytical tool for Sundanese wisdom. The sign-reading process is operationalized through the Pancaniti dialectical stages. The analysis results indicate that the elements of sajen do not stand randomly but form a structured sign system containing knowledge about cosmology, social ethics, and traditional ecology. Specifically, the Panca Curiga analysis reveals the connection between the sajen concept and the teachings of Sastra Jendra, the essence of which is the governance of harmony between humans and the universe. In conclusion, the sajen tradition in Pesta Laut can be understood as a custom-based environmental conservation mechanism and a rational local knowledge system. This study contributes methodologically by offering the operationalization of integrating modern semiotics and Panca Curiga as an interpretation model for Nusantara cultural text